Empowering Engagement Creating Learning Opportunities for Students from Challenging Backgrounds - Ng, Clarence (Springer International Publishing, 2018)
This book examines promoting engagement for children and adolescents from challenging contexts or who are dealing with challenging conditions. The volume concentrates on three vulnerable groups: marginalized youths who have experienced repeated exclusion and sought their second chance in alternative education; children who are coming from economically, culturally, and linguistically disadvantaged backgrounds; and students with social or emotional issues. It defines engagement as evolving over the course of learning, an interpersonal as well as personal process involving students, learning environment, teachers, and peers. Chapters identify the complex personal, sociocultural, economic, and systemic barriers that keep these vulnerable students from fully engaging in school, and explore the enabling role of collaborative and supported learning activities in building academic success and a foundation for productive adult lives. In addition, chapters present instructional practices based on engagement enablers. Chapters also pinpoint specific learning skills and subject areas that can provide openings for promoting motivation and participation. Featured topics include: The importance of cognitive and social enablers for promoting learning engagement. Engagement in instruction from teachers and testing within classrooms. Student voice and perspective as a reading engagement enabler. Promoting academic engagement and aspiration for challenging and advanced mathematics. Alternative educational programs for re-engaging marginalized youths who "don't fit". Empowering Engagement is a must-have resource for researchers, scientist-practitioners, clinicians, and graduate students in the fields of child and school psychology, educational policy and politics, social work, motivation and learning, schooling and pedagogies, and related disciplines.